2021
DOI: 10.1016/j.xcrm.2021.100457
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic T cell signaling by 41BB and CD28 is optimally achieved by membrane proximal positioning within parallel chimeric antigen receptors

Abstract: Summary Second generation (2G) chimeric antigen receptors (CARs) contain a CD28 or 41BB co-stimulatory endodomain and elicit remarkable efficacy in hematological malignancies. Third generation (3G) CARs extend this linear blueprint by fusing both co-stimulatory units in series. However, clinical impact has been muted despite compelling evidence that co-signaling by CD28 and 41BB can powerfully amplify natural immune responses. We postulate that effective dual co-stimulation requires juxta-membrane p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 65 publications
2
36
0
Order By: Relevance
“…We have recently demonstrated superior anti-tumor function of pCAR T-cells, in which a CD28-containing 2G CAR is co-expressed with a 4-1BB-containing CCR ( 10 ). To test the applicability of the pCAR platform to targeting of CD19, we co-expressed each of the mutant scFv-based 2G CARs described above with a 4-1BB CCR that contains an unmodified FMC63 scFv.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have recently demonstrated superior anti-tumor function of pCAR T-cells, in which a CD28-containing 2G CAR is co-expressed with a 4-1BB-containing CCR ( 10 ). To test the applicability of the pCAR platform to targeting of CD19, we co-expressed each of the mutant scFv-based 2G CARs described above with a 4-1BB CCR that contains an unmodified FMC63 scFv.…”
Section: Resultsmentioning
confidence: 99%
“…Cytolytic activity of all pCAR T-cell populations was similar or superior compared to the corresponding mutant scFv-based 2G CAR, or the F-2 CAR ( Figure 4B ). We have previously shown that a docking effect of the CCR can potentiate cytolytic activity of some, but not all pCARs, when compared to the parental CAR ( 10 ). Analysis of immune synapse formation by these T-cell populations could help to uncover mechanisms that may explain this variable response of pCAR T-cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dual CAR design can also be exploited to enhance signaling by 4-1BB and CD28 domains, which is best achieved by the membrane proximal positioning of both signaling units, within separate, parallel CAR [ 88 ].…”
Section: Main Challenges For Car-t Cell Therapy Against Solid Tumorsmentioning
confidence: 99%